Prevalence of Cognitive Impairment Amongst Older Adults and the Associated Risk Factors - Muhammed, Zana Faris; Hussain, Ali Hattem; Abdalrazak, Haitham Assem (Kurdistan Journal of Applied Research, 2024)
Cognitive impairment in older adults refers to a decline in mental abilities such as memory, attention, and problem-solving, often associated with aging. This study aimed to show the prevalence of cognitive impairment among older people and examine the risk factors in acquiring the disease. This cross-sectional, community-based study was implemented between August 2022 and August 2023. The study population involved older adults (n= 400) living in urban regions aged ≥60 years. A questionnaire used to collect sociodemographic data. Further, mini mental state examination tool to assess cognitive function, activities of daily living tool to assess physical functional capacity, patient health questionnaire-9 tool to identify depressive symptoms, Snellen chart to examine visual acuity and whispered voice test to examine hearing acuity were used. Chi-square test used to investigate the association between risk factors and cognitive impairment. The prevalence of cognitive impairment was 31.25% in examined community. The risk of the disease was higher in the following participants: age group 90-100 (71.4%), female (45.9%), unemployed (47.1%), having insufficient socioeconomic level (51.2%), being illiterate (49.3%), having low hearing acuity (77.4%), having sever functional impairment (78.6%), being widowed (56.8%), living with others rather than a spouse (54.4%), having low visual acuity (33.3%), and having depressive symptoms (65.1%). The severity of cognitive impairment is statistically significantly related to age group of 90-100 years old (80%), smokers (n = 21) is mostly mild [n=9/21 (42.85%)], the decrease in hearing acuity is more frequent among those with sever cognitive impairment [n= 9/24 (37.5%)], and most of the features were of mild severity [n= 45/69 (65.2%)]. Cognitive impairment is a prevalent disease, and the risk factors are being females, unemployed, have a low socioeconomic level, illiterate, and widowed. Moreover, the disease is substantially related with increasing age, low hearing and visual acuity, depressive symptoms, and physical functional impairment.